2008
DOI: 10.2308/acch.2008.22.2.241
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on the SEC’s Proposal to Accept Financial Statements Prepared in Accordance with International Financial Reporting Standards (IFRS) without Reconciliation to U.S. GAAP

Abstract: SYNOPSIS: The Securities and Exchange Commission (SEC) recently issued a call for comment on a proposal to accept financial statements prepared in accordance with International Financial Reporting Standards (IFRS) without reconciliation to U.S. GAAP. Accounting researchers have attempted to assess the quality of IFRS using different methods and criteria. While we are skeptical of drawing direct conclusions about the SEC’s proposal based on this research, there is adequate evidence that both IFRS and U.S. GAAP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…1 Hopkins et al (2008) suggest that the decision to eliminate the previously-required Form 20-F reconciliation between IFRS and U.S. GAAP for foreign registrants is premature because material differences exist between the two standards, because information in the reconciliation is currently impounded into stock prices, and because differential implementation and enforcement of standards across countries may reduce the comparability of financial reports across jurisdictions. 2 Jamal et al (2008Jamal et al ( , 2009) assert that there is no conclusive evidence that financial reports prepared using U.S. GAAP are better than reports prepared using IFRS, and recommend that the SEC allow U.S. companies to choose between IFRS and U.S. GAAP rather than mandate the adoption of IFRS. Similarly, Kothari et al (2010) provide a survey and economic analysis of the properties of GAAP and conclude that, rather than converging U.S. GAAP with IFRS, competition between the FASB and the IASB would allow GAAP to better respond to market forces.…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 95%
See 3 more Smart Citations
“…1 Hopkins et al (2008) suggest that the decision to eliminate the previously-required Form 20-F reconciliation between IFRS and U.S. GAAP for foreign registrants is premature because material differences exist between the two standards, because information in the reconciliation is currently impounded into stock prices, and because differential implementation and enforcement of standards across countries may reduce the comparability of financial reports across jurisdictions. 2 Jamal et al (2008Jamal et al ( , 2009) assert that there is no conclusive evidence that financial reports prepared using U.S. GAAP are better than reports prepared using IFRS, and recommend that the SEC allow U.S. companies to choose between IFRS and U.S. GAAP rather than mandate the adoption of IFRS. Similarly, Kothari et al (2010) provide a survey and economic analysis of the properties of GAAP and conclude that, rather than converging U.S. GAAP with IFRS, competition between the FASB and the IASB would allow GAAP to better respond to market forces.…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 95%
“…However, our results suggest that along at least one dimension -the ability to predict future cash flows -the quality of U.S. financial reporting may actually decline with the adoption of IFRS. We suggest that this difference in the ability to predict future cash flows supports calls for allowing competition between IFRS and U.S. GAAP rather than requiring all U.S. firms to adopt IFRS or converging IFRS and U.S. GAAP (Jamal et al, 2008(Jamal et al, , 2009Sunder, 2009;Bradshaw et al, 2010;Kothari et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, so far, there is insufficient evidence indicating that specific reporting standards would be superior to the other reporting standards (Jamal et al, 2008). Leuz (2003) and Bartov et al (2005) found that there is no significant difference between IFRS and US GAAP earnings.…”
Section: Consequences Of Ifrs Adoption: Foreign Issuersmentioning
confidence: 98%